2006
DOI: 10.1111/j.1574-6968.2006.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin protects endothelial cells against apoptotic cell death induced byPorphyromonas gingivaliscysteine proteinases

Abstract: Osteoprotegerin (OPG) is a key regulator of osteoclastogenesis during the progression of periodontitis. Recent reports suggest that osteoprotegerin may also prevent arterial calcification and contribute to endothelial cell survival. To determine whether the vascular functions of osteoprotegerin are involved in periodontitis, we examined whether osteoprotegerin contributed to the survival of endothelial cells damaged by Porphyromonas gingivalis cysteine proteinases (gingipains). Gingipain proteinases cleave a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…2c). The OPG survival effect has also been demonstrated in pathological conditions such as periodontitis [171]. Indeed, OPG produced by microvascular endothelial cells controls endothelial cell survival and bone remodeling during this pathology [172].…”
Section: Opg/rankl and Endothelial Cells: A Close Functional Relationmentioning
confidence: 97%
“…2c). The OPG survival effect has also been demonstrated in pathological conditions such as periodontitis [171]. Indeed, OPG produced by microvascular endothelial cells controls endothelial cell survival and bone remodeling during this pathology [172].…”
Section: Opg/rankl and Endothelial Cells: A Close Functional Relationmentioning
confidence: 97%
“…Several studies 2,[6][7][8][9][10] have demonstrated that recombinant OPG supports the survival of both normal and tumor-associated For personal use only. on March 31, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] More importantly, for the purpose of this study, it has also been shown that OPG is produced in vitro by vascular endothelial cells, is overexpressed by tumor-associated endothelial cells, and is able to promote the survival/proliferation of endothelial cells in a paracrine or autocrine manner. [6][7][8][9][10] Moreover, elevated levels of serum OPG have been detected in both solid tumors and hematologic malignancies. 11 Although the relative contribution of both normal and tumor-associated endothelial cells to serum OPG remains to be established, 2 both the stromal and the tumoral vasculature is engaged in extensive interactions with the cancer cells, probably contributing to the growth and invasiveness of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, OPG exerts an antiapoptotic effect towards TRAIL and decreases in consequence the number of apoptotic bodies that may serve as nucleation sites for passive mineralization (Fleishman et al 1990;Benslimane-Ahmim et al 2011). Several studies have shown also that recombinant OPG can promote the survival/proliferation of mature vascular endothelial cells (Malyankar et al 2000;Pritzker et al 2004;Cross et al 2006;Kobayashi-Sakamoto et al 2006;McGonigle et al 2009). Similarly, Lawrie et al showed OPG promotes the proliferation and the migration of pulmonary artery smooth muscle cell, and thus evidenced an important role of OPG in the pathogenesis of pulmonary arterial hypertension (Lawrie et al 2008).…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 99%